Persistence of insecticides against larvae of Plutella xylostella (L.) - Mohamad, Rosli; Ismail, Mohd. Yunus (Cambridge University Press, 1988)
Persistence of four insecticides (prothiofos, Bacillus thuringiensis Berliner, fenveralate and methamidophos) were evaluated against the larvae of Plutella xylostella (L.), under field conditions. The effective biological action of the chemicals against the larvae varied with different instars. The insecticides were biologically effective for 6 to 8 days after treatment against first and second instars, and their index of persistent toxicity was higher than that for third and fourth instars. They were effective against third and fourth instars only for one day after spraying. Prothiofos and B. thuringiensis were more toxic to all the instars than methamidophos or fenveralate